Facility-Based Assessment of NCD Service Preparedness at Sub-Centres in Satara District, Maharashtra - Mane, Amit A.; S. Patil, Supriya; R. Patil, Satish (Journal of Neonatal Surgery, 2025)
Background: Our world is facing a great challenge of tackling burden of non-communicable diseases (NCDs). India has to be prepared for tackling NCDs at both urban and rural populations in coming years. We have initiated many health initiatives towards this goal over the years. However, if the well-equipped and well-prepared health facilities are the basic foundation for any health initiatives. In this study we are going assess how well the sub centers in Satara District are ready to face NCDs. Material & Methods: This Facility based cross sectional study was conducted in 15 sub centers located in Satara District. Facilities were inspected to assess their readiness for implementation of NPCDCS in Satara district in accordance with IPHS standards and program guidelines. Statistical analysis was carried out using SPSS version 20. Institution ethical committee approved this study. This study was planned to assess their readiness to tackle NCDs through NPCDCS program in Satara district. Results: There were no dedicated staff positions created for program at SC level. However the number of staff working for NCDs was sufficient. Essential medicines required for NCDs were scarce. Also supply of consumables like dip sticks for urine test was not sufficient. Conclusion: Overall, the Sub Centre faced several challenges but also presented opportunities for improvement. These highlight the need to strengthen public education, standardize care protocols, upgrade infrastructure and equipment, and improve data management systems to effectively tackle non-communicable diseases (NCDs) in the community.